Le Brésil colonial : tropique de tous les péchés ? - Richard Marin (Les Cahiers de Framespa)
Most accounts of Brazil have characterized this country as one of bodily freedom and unbridled sexuality. In these tellings, the violence of the slave system, the intense miscegenation among Blacks, Indians, and Portuguese, the limited presence of the Catholic Church (largely unaffected by the Tridentine reform) mainly account for such behaviors. This paper, however, aims to explore and to qualify such descriptions, which have been shaped in part by Inquisition sources focusing on deviations and transgressions instead of ‘conventional’ sexuality and ordinary love relationships.